1980
DOI: 10.1055/s-2007-1021721
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoscopy in Upper Gastrointestinal Bleeding in Patients with Malignancy

Abstract: A retrospective review of upper gastrointestinal bleeding in 55 patients with malignant disease is presented here. Major causative factors seem to be superficial gastritis and gastric erosions. With aggressive endoscopy, a diagnostic accuracy of 90 percent has been achieved. However, having the exact diagnosis too often has little significance on the final outcome of these critically ill patients, unless therapy directed against bleeding can provide time for effective antineoplastic treatment. With the better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tumor-related gastrointestinal bleeding is currently a challenging clinical problem 1 . A retrospective review of upper gastrointestinal bleeding in 55 patients with primary or metastatic gastrointestinal malignancy revealed that up to 20 % were related to tumor invading gastrointestinal lumen and causing bleeding 2 . Currently, endoscopy is recommended as the main diagnostic tool to locate the site of bleeding 2 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-related gastrointestinal bleeding is currently a challenging clinical problem 1 . A retrospective review of upper gastrointestinal bleeding in 55 patients with primary or metastatic gastrointestinal malignancy revealed that up to 20 % were related to tumor invading gastrointestinal lumen and causing bleeding 2 . Currently, endoscopy is recommended as the main diagnostic tool to locate the site of bleeding 2 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review of upper gastrointestinal bleeding in 55 patients with primary or metastatic gastrointestinal malignancy revealed that up to 20 % were related to tumor invading gastrointestinal lumen and causing bleeding 2 . Currently, endoscopy is recommended as the main diagnostic tool to locate the site of bleeding 2 3 . Unfortunately, current endoscopic hemostatic methods including coaptation therapy, argon plasma coagulation, and mechanical hemostasis do not reliably control active bleeding, with rates of successful immediate hemostasis as low as 40 % and a significant short-term rebleeding rate (up to 30 %) 1 4 5 .…”
Section: Introductionmentioning
confidence: 99%